Precautions for Workers - Guest, G. H. (1948)
Radioactive isotopes are now available from Chalk River for use by Canadian biologists. Experience has shown that the handling of radioactive isotopes may involve health hazards unless adequate precautions are taken. The nature of these hazards and the type of precautions which must be taken when working with radioactive isotopes are considered. Successful work with radioactive isotopes other than in the smallest tracer amounts requires the use of laboratories and equipment especially designed for the purpose and this is dealt with briefly. The operation of a radioactive laboratory requires certain auxiliary equipment and services, such as health instruments, film monitoring, special laboratory clothing, special cleanable surfaces and disposal of radioactive waste materials. These topics are discussed briefly. Handling of radioactive isotopes involves certain special precautions and a few of these, such as protection of hands, cleaning of glassware, handling of solutions, etc. are reviewed. In addition to protecting all personnel in a laboratory from harmful amounts of radiation, it is necessary to keep the laboratory and the building in which it is housed as free as possible from radioactive substances and this important fact has been stressed.